Effects of plant biomass on denitrifying genes in subsurface-flow constructed wetlands - Chen, Yi; Wen, Yue; Zhou, Qi; Vymazal, Jan (Bioresource technology, 2014)
The effect of Typha latifolia and its litter on density and abundance of three denitrifying genes (nirS, nirK and nosZ) were investigated in six laboratory-scale SSF CW microcosms. Results showed that the copy numbers of nirS, nirK and nosZ in wetland microcosms were ranged between 10(8)-10(9), 10(6)-10(7) and 10(7)-10(8) copies g(-1), respectively. The presence of T. latifolia encouraged the growth of nirK containing bacteria. Addition of cattail litter could greatly stimulate the growth of bacteria containing nirS and nosZ gene. Path analysis illustrated that the presence of plants and litters had no significant direct impact on denitrifying genes, while it affected the denitrifying genes via alteration of dissolved oxygen and carbon sources.
Keywords: rostliny; mokřady; RNA, Ribosomal, 16S; Denitrifying genes; Cattail litter; Typha latifolia; Denitrification; Bacteria; Nitrate removal; nitrátreduktasa; Subsurface flow constructed wetlands (SSF CWs); bakteriální geny; Plants; Models, Biological; Wetlands; RNA ribozomální 16S; denitrifikace; biologické modely; Genes, Bacterial; Biomass; Nitrate Reductase; biomasa